HIDUP HARMONIS: KAWASAN WISATA ALAM SEBAGAI MEDIA PEMBELAJARAN PENGALAMAN BUDAYA SUNDA - Wandi Krisdian; Asep Yudi Permana; Mokhammad Syaom Barliana (Jurnal Arsitektur ZONASI, 2022)
Abstract: In their culture, Sundanese people recognize the concept of 3 certainty of life as a philosophy of life, which is known as "Tritangtu". The concept of life is interrelated and cannot be separated to achieve a harmonious life between humans and their natural surroundings. This study was conducted using a qualitative descriptive method with a literative study technique and a direct survey. The purpose of this study is to produce a design for a mountainous tourist area as a medium for teaching and developing the noble values of Sundanese culture. The phenomenon of the Indonesian nation today tends to lose its character and sociality, so that the development and teaching of cultural values is very much needed. Teaching with experiential learning methods in a tourist area as a medium, will facilitate understanding of these noble values. Just as the ancestors passed on Sundanese culture to their next generation through direct experience in the form of art, pupuh, pikukuh etc. Only by re-adhering to one's own culture, a harmonious life and character of a nation will be achieved. Keywords: Tritangtu, Culture, Sundanese, Ecotourism Abstrak: Dalam kebudayaannya, orang sunda mengenal konsep 3 kepastian hidup sebagai falsafah hidupnya, yang dikenal dengan nama “Tritangtu”. Konsep hidup yang saling berkaitan dan tak bisa dipisahkan untuk mencapai kehidupan yang harmonis antara manusia dan alam sekitarnya. Kajian ini dilakukan dengan metode deskriptif kualitatif dengan teknik kajiannya secara literatif dan survey langsung. Tujuan dari kajian ini adalah untuk menghasilkan suatu rancangan kawasan wisata pegunungan sebagai media pengajaran dan pengembangan nilai-nilai luhur budaya sunda. Fenomena bangsa Indonesia saat ini cenderung kehilangan karakter dan kesosialannya, sehingga pengembangan dan pengajaran nilai budaya sangat diperlukan. Pengajaran dengan metode pembelajaran pengalaman pada suatu kawasan wisata sebagai medianya, akan mempermudah pemahaman akan nilai luhur tersebut. Seperti halnya para leluhur mewariskan budaya sunda ke generasi penerusnya lewat pe-ngalaman langsung berupa kesenian, pupuh, pikukuh dsb. Hanya dengan kembali berpegang pada budaya sendiri, maka kehidupan harmonis dan berkarakter suatu bangsa akan tercapai. Kata Kunci :  Tritangtu, Budaya, Sunda, Ekowisata